Preferential regional distribution of atrial fibrosis in posterior wall around left inferior pulmonary vein as identified by late gadolinium enhancement cardiac magnetic resonance in patients with atrial fibrillation. Issue 12 (31st May 2018) - Benito, Eva M; Cabanelas, Nuno; Nuñez-Garcia, Marta; Alarcón, Francisco; Figueras I Ventura, Rosa M; Soto-Iglesias, David; Guasch, Eduard; Prat-Gonzalez, Susanna; Perea, Rosario J; Borràs, Roger; Butakoff, Constantine; Camara, Oscar; et al.
Abstract: Aims: Left atrial (LA) fibrosis can be identified by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) in patients with atrial fibrillation (AF). However, there is limited information about anatomical fibrosis distribution in the left atrium. The aim is to determine whether there is a preferential spatial distribution of fibrosis in the left atrium in patients with AF. Methods and results: A 3-Tesla LGE-CMR was performed in 113 consecutive patients referred for AF ablation. Images were post-processed and analysed using ADAS-AF software (Galgo Medical), which allows fibrosis identification in 3D colour-coded shells. A regional semiautomatic LA parcellation software was used to divide the atrial wall into 12 segments: 1–4, posterior wall; 5–6, floor; 7, septal wall; 8–11, anterior wall; 12, lateral wall. The presence and amount of fibrosis in each segment was obtained for analysis. After exclusions for artefacts and insufficient image quality, 76 LGE-MRI images (68%) were suitable for fibrosis analysis. Segments 3 and 5, closest to the left inferior pulmonary vein, had significantly higher fibrosis (40.42% ± 23.96 and 25.82% ± 21.24, respectively; P < 0.001), compared with other segments. Segments 8 and 10 in the anterior wall contained the lowest fibrosis (2.54% ± 5.78 and 3.82% ± 11.59, respectively; P < 0.001). Age >60 years was significantly associated with increased LA fibrosis [95% confidence interval (CI) 0.19–8.39, P = 0.04] and persistent AF approached significance (95% CI −0.19% to 7.83%, P = 0.08). Conclusion: In patients with AF, the fibrotic area is preferentially located at the posterior wall and floor around the antrum of the left inferior pulmonary vein. Age >60 years was associated with increased fibrosis.